The gallery - Fitzgerald, Laura Marx (New York, NY : Dial Books for Young Readers, 2016)
In 1929 New York City, twelve-year-old housemaid Martha O'Doyle suspects that a wealthy recluse may be trying to communicate with the outside world through the paintings on her gallery walls.
Keywords: Mystery and detective stories; Household employees -- Fiction; Art -- Fiction; Irish Americans -- Fiction; New York (N.Y.) -- History -- 1898-1951 -- Fiction; Household employees -- Juvenile fiction; Art -- Juvenile fiction; Irish Americans -- Juvenile fiction; New York (N.Y.) -- History -- 1898-1951 -- Juvenile fiction; Detective and mystery fiction